BENDI: Improving Cognitive Assessments in Toddlers and Children with Down Syndrome Using Stealth Assessment - Marcela Tenorio; Paulina S. Arango; Andrés Aparicio (MDPI AG, 2023)
Cognitive assessment is a fundamental step in diagnosing intellectual and developmental disabilities, designing interventions, and evaluating their impact. However, developed and developing countries have different access to tools designed for these purposes. Our goal was to develop a battery for cognitive assessment mediated by digital technology that allows the exploration of cognitive domains (inhibitory control, attention, motor ability, and context memory) in children with Down Syndrome (DS) in Chile. Four tasks, based on established experimental paradigms modified to provide a game-like experience, were tested in 68 children with DS from 20 months to 12 years of age. We present evidence of reliability based on internal consistency and split-half analyses, with results ranging from adequate to excellent. Regarding validity, factorial and correlational analyses show evidence consistent with what was theoretically expected of internal structure, convergence, and divergence with other measures. Expected age trajectories were observed as well. Our data offer evidence that supports the use of tasks based on touch-screen devices for cognitive assessment in the population with DS. The tasks also have a low cultural load, so they could be validated and used in other contexts without the need for an adaptation process.